2016
DOI: 10.1091/mbc.e16-01-0032
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of ATM upon DNA-PKcs inhibition modulates p53 dynamics and cell fate in response to DNA damage

Abstract: Time-resolved single-cell analysis and pharmacological perturbations reveal a new regulatory interplay between PI3K-like kinases in response to DNA double-strand breaks: upon loss of DNA-PKcs activity, ATM is hyperactivated and induces an amplified p53 response, which sensitizes cells for damage-induced senescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 36 publications
6
71
0
Order By: Relevance
“…Consistent with our observations, increased global phosphorylation of H2AX as well as higher enrichment of γH2AX at AsiSI-induced DSBs have been observed in U2OS cells upon DNA-PKi treatment (Caron et al, 2015). Hyperactivation of ATM upon DNA-PKcs inhibition is also reported in A549 and MCF10A cells after IR treatment (Finzel et al, 2016). Notably, this effect was not observed when the NHEJ pathway was inhibited by DNA Ligase IV inhibitor, suggesting that an increase in DSBs alone is not sufficient for ATM hyperactivation upon DNA-PKcs inhibition (Finzel et al, 2016).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Consistent with our observations, increased global phosphorylation of H2AX as well as higher enrichment of γH2AX at AsiSI-induced DSBs have been observed in U2OS cells upon DNA-PKi treatment (Caron et al, 2015). Hyperactivation of ATM upon DNA-PKcs inhibition is also reported in A549 and MCF10A cells after IR treatment (Finzel et al, 2016). Notably, this effect was not observed when the NHEJ pathway was inhibited by DNA Ligase IV inhibitor, suggesting that an increase in DSBs alone is not sufficient for ATM hyperactivation upon DNA-PKcs inhibition (Finzel et al, 2016).…”
Section: Resultsmentioning
confidence: 89%
“…Hyperactivation of ATM upon DNA-PKcs inhibition is also reported in A549 and MCF10A cells after IR treatment (Finzel et al, 2016). Notably, this effect was not observed when the NHEJ pathway was inhibited by DNA Ligase IV inhibitor, suggesting that an increase in DSBs alone is not sufficient for ATM hyperactivation upon DNA-PKcs inhibition (Finzel et al, 2016). Taken together, these results suggest that DNA-PKcs negatively regulates ATM activation upon DNA damage in mammalian cells.…”
Section: Resultsmentioning
confidence: 89%
“…More dynamical p53 patterns have been identified depending on the radiation type and dose [10, 13, 14]. A most recent finding by Finzel et al has demonstrated a novel p53 dynamics in response to DNA damage [15]. Their study argues that ATR or DNA-PK alone could compensate for the deficiency in the other two PI3K-like members and retain regular p53 dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Their study argues that ATR or DNA-PK alone could compensate for the deficiency in the other two PI3K-like members and retain regular p53 dynamics. Instead, in the absence of DNA-PK, p53 reacts more strongly to ATM mediated phosphorylation with escalated first pulses [15]. ATM is hyper-activated when catalytic DNA-PK activity is blocked, implying that DNA-PK may inhibit ATM kinase activity [15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation